Pengaruh Kualitas Pelayanan, Harga, dan Store Atmosphere terhadap Keputusan Pembelian Konsumen di Rocket Chicken Cabang Ngronggo Kota Kediri (International Forum of Researchers and Lecturers, 2025)
This study aims to analyze the influence of service quality, price, and store atmosphere on consumer purchasing decisions at the Rocket Chicken branch in Ngronggo, Kediri City. These three variables were chosen because they are considered to play an important role in influencing consumer behavior, particularly in the context of the increasingly competitive fast food industry. Service quality includes aspects of friendliness, speed, and accuracy of service provided by employees to customers. Price is considered in terms of affordability, suitability with product quality, and competitiveness compared to competitors. Meanwhile, store atmosphere includes cleanliness, lighting, layout, comfort, and the overall ambiance perceived by consumers when they are in the outlet. The research method used is quantitative with a survey approach. Data was obtained through the distribution of closed questionnaires to 130 respondents who are active consumers of Rocket Chicken at the research location. The data analysis technique used is multiple linear regression with the help of the latest version of SPSS software, in order to determine the extent of the influence of each independent variable on the dependent variable, namely purchasing decisions.The research results indicate that service quality, price, and store atmosphere significantly influence consumer purchasing decisions, both partially and simultaneously. These findings provide important implications for Rocket Chicken's management to pay more attention to these factors in formulating marketing strategies and operational management, in order to enhance customer satisfaction, loyalty, and appeal in the future.